IM Twenty-Four Steps Of Educational Innovation In Indonesia: Twenty-Four Steps Of Educational Innovation In Indonesia - Miftakhu Niamah; Jauhan Budiwan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to critically analyze educational innovation in Indonesia through twenty-four appropriate educational strategies. This type of research is library research. Collecting data by identifying discourse from books, papers or articles, journals, newspapers, the internet (web), or other information related to education. Data analysis used descriptive analysis, content analysis, and scientific critical analysis. The results of the study show that educational innovation in Indonesia can implement twenty-four educational strategies which include Personalization, Multi-Age Classes, Small Community Learning, Peer Group Learning, Small Group Learning Communities with other groups, Multidisciplinary Curriculum with Block Scheduling, Cooperative Learning, Cooperative Learning, Project Based Learning, Co-Teachers, Teaching Teams, Community Service Learning, Looping Partnerships, Business for Assessment, Resources, and Funding, Global Connections, Laptops, and Wireless Technology for Anywhere, Anytime Learning, Parental Involvement, Students Putting on Shows, Curriculum Life Skills (Non-Academic), Meaningful Career Counseling, Social/Emotional Counseling, Open Learning, Education to Serve Student Needs, Portfolio-Based Assessment and New Paradigm of School Buildings.